Evolution of Stupas in Burma: Pagan Period: 11th to 13th Centuries A.D. - Teekoy, Mathew C (Journal of Dharma, 1992)
Sujata Soni, Evolution of Stupas in Burma; Pagan Period: 11th to 13th Centuries, A.D., Delhi: Motilal Banarsidas, 1991 , pp. 1 13+71 pages of plates.